2018
DOI: 10.1159/000487482
|View full text |Cite
|
Sign up to set email alerts
|

"Real-life" Efficacy and Safety Aspects of 4-Year Omalizumab Treatment for Asthma

Abstract: Significance of the Study• In this study, the long-term efficacy and safety of omalizumab therapy in asthma were evaluated in a real-life setting. Omalizumab therapy resulted in better asthma control, and was effective and well tolerated as an add-on therapy for patients with moderate-to-severe asthma. The number of excellent responders increased from 35 (53.8%) at 16 weeks to 48 (73.8%) at the 4-year follow-up. The number of patients who did not require ERV improved from 0 to 59 (90.8%), and the lowest rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Such important results, referring to placebo-controlled studies, have been also confirmed and expanded by a very large body of real-life investigations carried out worldwide, 80 93 which have been systematically reviewed by Abraham and colleagues and by Alhossan and colleagues. 94 , 95 These authors have clearly shown that many patients with severe allergic asthma can be defined as ‘good’ or ‘excellent’ responders to omalizumab with regard to decreases in disease exacerbations, hospital admissions, and overall intake of both oral and inhaled corticosteroids, as well as with regard to improvements in asthma symptoms, pulmonary function, and quality of life.…”
Section: Add-on Therapy Of Severe Asthma With Omalizumabmentioning
confidence: 71%
See 1 more Smart Citation
“…Such important results, referring to placebo-controlled studies, have been also confirmed and expanded by a very large body of real-life investigations carried out worldwide, 80 93 which have been systematically reviewed by Abraham and colleagues and by Alhossan and colleagues. 94 , 95 These authors have clearly shown that many patients with severe allergic asthma can be defined as ‘good’ or ‘excellent’ responders to omalizumab with regard to decreases in disease exacerbations, hospital admissions, and overall intake of both oral and inhaled corticosteroids, as well as with regard to improvements in asthma symptoms, pulmonary function, and quality of life.…”
Section: Add-on Therapy Of Severe Asthma With Omalizumabmentioning
confidence: 71%
“… 96 , 97 The relevant benefits obtained in terms of symptom control and lung function, evaluated as significant increases in asthma control test (ACT) score and FEV 1 , respectively, persist and progressively improve during long-term (1–4 years) treatment with omalizumab. 93 Such remarkable improvements including very important clinical, functional, and corticosteroid-sparing effects, associated with a good safety and tolerability profile, have been shown to persist after 7 and even 9 years of anti-IgE therapy. 98 100 In addition to corroborating these convincing findings, further data have been obtained by real-life studies.…”
Section: Add-on Therapy Of Severe Asthma With Omalizumabmentioning
confidence: 99%
“… 6–10 In addition to efficacy, an excellent safety profile has also been confirmed over time, even in fragile patients and under particular conditions, so much so that omalizumab can even be administered to pregnant women. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…Schistosome was one of the parasites that have been found to have protective effects against autoimmune diseases and allergies such as arthritis and asthma ( Osada et al, 2009 ; Janssen et al, 2016 ; Qiu et al, 2017 ). These explorations hold great promise in identifying a new and more specific intervention measure for atopic asthma that does not result in certain side effects, such as increased susceptibility to infection and necrosis, which can be triggered by steroid hormone drugs such as dexamethasone ( Kuprys-Lipinska and Kuna, 2014 ; Al-Ahmad et al, 2018 ; Falk, 2018 ).…”
Section: Introductionmentioning
confidence: 99%